E-attachment and Online Communication The Changing Context of the Clinical Diagnosis and Psychological Treatment - Sitnik-Warchulska, Katarzyna (Explorations in Mental Health, 2023)
This book examines the use of modern technologies in clinical psychological practice. It considers how we define attachment in an age where changes in technology and the COVID-19 pandemic have increased the prevalence of online contact in the process of diagnosis and psychological treatment. Based on an attachment paradigm that is relatively unexplored, the book outlines how modern online contact influences mental health and development, along with the therapeutic relationship between client and professional. It discusses people's relationships with new technologies, how relationships can be established using these technologies, and how these technologies affect professional relationships between psychologists and their clients, which they define as e-attachment. In the context of new technologies, the book draws on neurobiology and clinical psychology to consider mental health, social functioning, and emotional regulation. Presenting both theory and examples from case studies, this cutting-edge book will be of great interest to researchers, academics, and post-graduate students in the fields of clinical psychology, psychotherapy, and mental health. Those also carrying out research into digital and online learning within the field of mental health will also benefit from this text. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license